Empathy in subjects with high intellectual potential (HIP): Rethinking stereotypes through a multidimensional and developmental review - Lavenne-Collot, Nathalie; Planche, Pascale; Vaivre-Douret, Laurence (Intelligence (Norwood), 2025)
Empathy is often portrayed as a defining trait of individuals with High Intellectual Potential (HIP), frequently associated with heightened sensitivity, emotional depth, or altruistic tendencies. However, such generalizations oversimplify a multidimensional construct and overlook intra-group variability in empathic functioning. This review adopts a multidimensional and developmental perspective to examine empathy in HIP individuals. Drawing on cognitive neuroscience, developmental psychology, and psychopathology, it analyzes how emotional, motivational, cognitive, regulatory, and embodied components of empathy interact with high-level intellectual functioning. Specific focus is placed on developmental asynchrony, contextual modulation, and the cognitive–emotional balance of empathy. Current evidence suggests that empathy in HIP individuals may not conform to a uniform pattern. Rather, diverse and dynamic configurations appear to emerge, potentially involving a relative dominance of cognitive empathy (CE) over emotional empathy (EE), modulated by regulatory capacities, sensory traits, motivational states, and contextual demands. While such profiles could support analytical detachment in emotionally charged situations, they might also limit affective attunement. These possible configurations—some of which may intersect with neurodevelopmental or psychopathological traits—underscore the need for cautious interpretation, subgroup differentiation, and further empirical investigation. Understanding empathy in HIP individuals requires a flexible, integrative framework that accounts for developmental plasticity, regulatory diversity, and contextual influences. Such an approach refines empathy models and supports individualized interventions in educational and clinical settings. Future research should prioritize ecologically valid, embodied, and neurophysiological methods to better capture empathic variability across developmental stages. •Empathy in HIP individuals is explored through a multidimensional, developmental lens.•Cognitive-emotional imbalances may emerge in specific HIP profiles.•Regulatory mechanisms can promote cognitive empathy over affective resonance.•Empathic configurations may overlap with neurodevelopmental or psychopathological traits.•Context-sensitive and embodied methods are needed to investigate empathic diversity